Managing the veterinary input on large dairy herds. Issue 6 (11th July 2019) - Reader, Jon
Abstract : This article sets out some of the main considerations and challenges for managing the veterinary input in large dairy herds. It focuses on the way that the veterinarian can satisfy the demands of the modern day dairy farmer while facilitating an expert team on the farm, including the targeted use of paraprofessionals working in conjunction with the vet to provide a cost‐effective but professional service.